Chemogenetic suppression of anterior cingulate cortical neurons projecting to the visual cortex disrupts attentional behavior in mice - Kevin J. Norman; Hiroyuki Koike; Sarah E. McCraney; Yury Garkun; Julia Bateh; Elisa N. Falk; Susanna Im; Keaven Caro; Michael P. Demars; Hirofumi Morishita (Wiley, 2021)
Abstract Aim Attention is a goal‐directed cognitive process that facilitates the detection of task‐relevant sensory stimuli from dynamic environments. Anterior cingulate cortical area (ACA) is known to play a key role in attentional behavior, but the specific circuits mediating attention remain largely unknown. As ACA modulates sensory processing in the visual cortex (VIS), we aim to test a hypothesis that frontal top‐down neurons projecting from ACA to VIS (ACAVIS) contributes to visual attention behavior through chemogenetic approach. Methods Adult, male mice were trained to perform the 5‐choice serial reaction time task (5CSRTT) using a touchscreen system. An intersectional viral approach was used to selectively express inhibitory designer receptors exclusively activated by designer drugs (iDREADD) or a static fluorophore (mCherry) in ACAVIS neurons. Mice received counterbalanced injections (i.p.) of the iDREADD ligand (clozapine‐N‐oxide; CNO) or vehicle (saline) prior to 5CSRTT testing. Finally, mice underwent progressive ratio testing and open field testing following CNO or saline administration. Results Chemogenetic suppression of ACAVIS neuron activity decreased correct task performance during the 5CSRTT mainly driven by an increase in omission and a trending decrease in accuracy with no change in behavioral outcomes associated with motivation, impulsivity, or compulsivity. Breakpoint during the progressive ratio task and distance moved in the open field test were unaffected by ACAVIS neuron suppression. CNO administration itself had no effect on task performance in mCherry‐expressing mice. Conclusion These results identify long‐range frontal‐sensory ACAVIS projection neurons as a key enactor of top‐down attentional behavior and may serve as a beneficial therapeutic target.